Environmental Education for Students from School to University: Case Study on Biorefineries - Sergio Nogales-Delgado; José María Encinar Martín (MDPI AG, 2019)
Universities play an important role in society. On the other hand, more and more governments and international organizations are concerned about the environment. Thus, both in their educational programs and research, as well as in the case of public exhibitions, universities are increasingly including subjects related to the environment and its preservation. In the case of Spain, there are fewer university students than ten years ago (from approximately 140,000 to fewer than 130,000), and the number of students interested in technical and scientific degrees has equally decreased. Consequently, the importance of fostering a scientific culture with concerns in environmental issues is continuously increasing, from schools to universities. The role of real scientific environments, such as laboratories devoted to scientific research, could be an important support for environmental divulgation, as most research carried out at universities have to do with these subjects. The aim of this work was to show a specific case of environmental education in a laboratory devoted to the production of biodiesel and biolubricants, covering a wide range of academic levels and, depending on the audience, selecting the right content (both theoretical and practical). This guide was useful for the laboratory technicians, increasing the interest of the audience (considering the expositions good or excellent, depending on the academic level, and gaining enough or excellent knowledge about biorefineries).